Euryalida (Echinodermata, Ophiuroidea) from Northwest Africa - Calero, Belén; Ramil, Fran (European Journal of Taxonomy, 2023)
From 2004 to 2012, ten multidisciplinary oceanographic surveys were conducted along the coast of Northwest Africa, between the Strait of Gibraltar and the northern border of Sierra Leone. A total of five species of Euryalida Lamarck, 1816 belonging to three families were captured at 29 of the 1298 stations sampled in the area. Among them, Astrodendrum juancarlosi sp. nov. is described and figured in this paper. Ophiocreas oedipus Lyman, 1879 is recorded for the first time on West African continental margin and Gorgonocephalus pustulatum (H.L. Clark, 1916), an Indo-Pacific species only known from South African coast in the Atlantic, is reported off Guinea-Bissau, greatly extending to the North its Atlantic distribution. In addition, Asteroschema inornatum Koehler, 1906, a northeast Atlantic species, is recorded for the first time in African waters, off Western Sahara, extending its range of distribution to the south. Our data also extend the bathymetric distribution of A. inornatum to shallower waters and of G. pustulatum to deeper waters. The association of some euryalids with certain species of pennatulaceans and gorgonians is also described.